Wednesday

March 4, 2015

March 4, 2015

Posted by **COFFEE** on Saturday, July 28, 2007 at 1:02pm.

f(x) = x3, a = -1

and what i've done so far:

f (x) = x^3

f ' (x) = 3x^2

f '' (x) = 6x^1

f ''' (x) = 6x

f (-1) = -1

f ' (-1) = 3

f '' (-1) = -6

f ''' (-1) = -6

using taylor series equation.. my final answer that was wrong:

((-1(x+1)^0)/(0!))+((3(x+1)^1)/(1!))+((-6(x+1)^2)/(2!))+((-6(x+1)^3)/(3!))

.. is this what the question was asking for? if not, what is it then? thank you very much for your assistance.

f ''' (x) = 6

f'''(-1) = 6

- Calculus - Taylor #2 -
**Steve**, Tuesday, September 24, 2013 at 4:24amLooks good, assuming your arithmetic is ok.

**Answer this Question**

**Related Questions**

calculus - how do i use a taylor series centered at some x value to approximate ...

Calc 2 taylor series - use the definition of a taylor series to find the Taylor ...

Math - Hi Trying to work with confusing Taylor series....any assistance would be...

calculus repost, please assist pleassssssse - Hi Trying to work with confusing ...

Calculus - a) Find the Taylor series associated to f(x) = x^-2 at a = 1. Be sure...

calculus-- need help desperately! - The Taylor series about x=5 for a certain ...

Calculus Derivative- Taylor Series? - let f(x)= x/x-1 find f'(x) f ''(x) and a ...

Taylor seires - f(x) =ln (1-x) a) Compute f'(x), f''(x), f'''(x). Spot the ...

Calculus - By recognizing each series below as a Taylor series evaluated at a ...

Calculus - Please.... I need your help! I posted this question yesterday and no ...